Nephrology secrets - Lerma, Edgar V.; Sparks, Matthew A.; Topf, Joel M. (Secrets series, 2019)
"For more than 30 years, the highly regarded Secrets Series has provided students and practitioners in all areas of health care with concise, focused, and engaging resources for quick reference and exam review. Nephrology Secrets, 4th Edition, features the Secrets' popular question-and-answer format that also includes lists, tables, and an easy-to-read style - making reference and review quick, easy, and enjoyable"--Publisher's description